Electronic structure of 4d impurities in Rb: A local-spin-density approximation+U density-functional study - N. Stefanou (Journal of Physics: Condensed Matter, 1994)
The electronic structure of the 4d substitutional impurities in Rb is studied by means of self-consistent density functional calculations. Exchange and correlation corrections for localized orbitals, as included in the mean-field solution of Anderson's model, are superimposed on the spin-dependent potential of the traditional local-spin-density approximation. We find ionic-like dn configurations and a quite important spin polarization of the extended sp states. For Nb and Ru impurities we obtain two stable configurations in each case and their energetic stability is studied by means of constrained density-functional calculations. Our results are compared with the results of other calculations and with the available experimental data.